Janeway's immunobiology - Murphy, Kenneth (Kenneth M.); Weaver, Casey; Berg, Leslie; Barton, Gregory; Janeway, Charles A. (New York, NY : W.W. Norton and Company, 2022)
Immunobiology is the premier text for immunology at the advanced undergraduate, graduate, and medical school levels. Beginning students appreciate the book's clear writing and informative illustrations, while advanced students and working immunologists value its comprehensive scope. Every chapter is reviewed with experts to ensure accuracy, authority, currency, and depth. The Tenth Edition is supported by InQuizitive, Norton's award-winning, easy-to-use adaptive learning tool that helps students learn immunological terms and apply them conceptually. -- Provided by publisher.
Part I : An Introduction to Immunobiology and Innate Immunity -- Chapter 1 : Basic Concepts in Immunology -- Chapter 2 : Innate Immunity : The First Lines of Defense -- Chapter 3 : Cellular Mechanisms of Innate Immunity -- Part II : The Recognition of Antigen -- Chapter 4 : Antigen Recognition by B-cell and T-cell Receptors -- Chapter 5 : The Generation of Lymphocyte Antigen Receptors -- Chapter 6 : Antigen Presentation to T Lymphocytes -- Part III : The Development of Mature Lymphocyte Receptor Repertoires -- Chapter 7 : Lymphocyte Receptor Signaling -- Chapter 8 : The Development of B and T Lymphocytes -- Part IV : The Adaptive Immune Response -- Chapter 9 : T Cell-Mediated Immunity -- Chapter 10 : The Humoral Immune Response -- Chapter 11 : Integrated Dynamics of Innate and Adaptive Immunity -- Chapter 12 : The Barrier Immune System -- Part V : The Immune System in Health and Disease -- Chapter 13 : Failures of Host Defense Mechanisms -- Chapter 14 : Allergic Diseases and Hypersensitvity Reactions -- Chapter 15 : Autoimmunity and Transplantation -- Chapter 16 : Manipulation of the Immune Response -- Appendix I : The Immunologist's Toolbox
Includes online access.
Previous edition: published as by Kenneth Murphy, Casey Weaver. New York: Garland Science, 2017.
Includes bibliographical references and index.
Keywords: Immune System -- physiology; Immune System -- physiopathology; Immunity; Immunotherapy